Modelling the 4D kinematics of extensional structures developed above discontinuous inclined ductile basal detachments. (April 2022) - Carboni, F.; Koyi, H.; Bicocchi, A.; Barchi, M.R.
Abstract: A series of scaled analogue models were used to a preliminary study on the influence of the basal detachment configuration on the evolution of extensional systems, developed above an inclined basal ductile detachment. Three different basal configurations were aimed to test extension above: i) a homogeneously distributed ductile detachment; ii) two sectors with a different distribution of the ductile detachment, separated by an abrupt, transversal boundary; ii) a laterally variable width of the ductile detachment, driven by an abrupt oblique boundary. Fault activity was monitored through a series of digital elevation models obtained from the laser scanning of the models' surface. Results of the models analysis show how the geometry, the distribution, the kinematic, and the timing of faulting is strongly controlled by the geometry and orientation of the ductile-brittle interface in respect to the extension direction. Faults close to the brittle-ductile interface develop following the interface geometry, whose effect is reduced moving away from it. In addition, we observe a major number of faults which accommodates lower amount of extension and are less closely spaced above longer ductile detachments. Our results can be compared with natural case-histories along continental passive margins, where extension occurs above a dipping salt detachment, with inhomogeneous distribution (e.g., the northern Gulf of Mexico, central Brazilian margin, Angola margin). Highlights: Faults formed close to the brittle/ductile interface trend parallel to it. Dip-slip dominates along faults parallel to the brittle/ductile interface. Strike-slip dominates along faults oblique to the brittle/ductile interface. The effect of the brittle/ductile interface decreases away from it.